(3CbhGd hCTYGQ ZfGFjIs - (3fGUQ GdOjf GdYLejs
(3ChdgG (B:s
(3GdMeO ddg jTJed Ydi JUGfja hCbhGd hCTYGQ efJNHI ef s
(3BNQgG (B:s
(3bQHg ZGjI bUOi hGdLaG hGdHYO bUO s
(3Vef eLehY , JQJjHgG (B: (3GdChds
(3CbhGd hCTYGQ efJNHI ef CbhGd GdeJbOejfs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3afhf LejdI (B509) s
Keywords: (3GdehSjbi hGdZfGAs